Analisis faktor yang berhubungan dengan kepesertaan jaminan kesehatan nasional - Riana, Riana; Sanyoto, Didik Dwi; Ilmi, Bahrul; Febriana, Silvia Kristanti Tri; Herawati, Herawati (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: National health insurance is a program that is able to increase the achievement of Universal Health Coverage (UHC) and can help create optimal health levels. As for the data on national health insurance participation in Banjar Regency, which is still low, national health insurance participation in the Martapura 1 Health Center working area is still below 50% of the total population. Purpose: To analyze factors related to participation in national health insurance. Method: This study is quantitative with an observational analytical cross-sectional research design. The study was conducted in the Martapura 1 Health Center Working Area. The sampling technique used probability sampling technique with the cluster proportional random sampling method and the number of samples was 110 respondents. Data analysis used univariate, bivariate, and multivariate analysis. Bivariate analysis used the chi-square test and multivariate analysis used multiple logistic regression test. Results: There is no relationship between geographic accessibility and national health insurance participation (p-value = 0.300). However, there is a relationship between perception (p-value = 0.000), family support (p-value = 0.000), income (p-value = 0.047), and information accessibility (p-value = 0.029). The most dominant related variable is the family support variable with an Exp (B) value of 6.891. Conclusion: There is no relationship between geographic accessibility and national health insurance participation. However, there is a relationship between perception, family support, income, and information accessibility and the most dominant relationship is family support with national health insurance participation. Suggestion: The public is expected to be more concerned and think positively about the national health insurance program and actively participate. The Health social security agency needs to strengthen socialization, especially through social media. Keywords: Family Support; Income; Information Accessibility; National Health Insurance; Perception. Pendahuluan: Jaminan kesehatan nasional (JKN) adalah program yang mampu meningkatkan pencapaian Universal Health Coverage (UHC) dan dapat membantu menciptakan derajat kesehatan yang optimal. Adapun pada data kepesertaan JKN di Kabupaten Banjar yang masih rendah kepesertaan JKN yaitu di wilayah kerja Puskesmas Martapura 1 masih mencapai dibawah 50% dari total jumlah penduduk. Tujuan: Untuk menganalisis faktor yang berhubungan dengan kepesertaan jaminan kesehatan nasional. Metode: Penelitian ini bersifat kuantitatif dengan desain penelitian observasional analitik cross sectional. Penelitian dilakukan di Wilayah Kerja Puskesmas Martapura 1. Teknik pengambilan sampel menggunakan teknik probability sampling dengan metode cluster proporsional random sampling dan jumlah sampel sebanyak 110 responden. Analisis data menggunakan analisis univariat, bivariat, dan multivariat. Analisis bivariat menggunakan uji chi-square dan analisis multivariat menggunakan uji regresi logistik ganda. Hasil: Tidak terdapat hubungan antara keterjangkauan geografi dengan kepesertaan JKN (p-value=0.300). Namun, ada hubungan antara persepsi (p-value=0.000), dukungan keluarga (p-value=0.000), pendapatan (p-value=0.047), dan aksesibilitas informasi (p-value=0.029). Adapun variabel yang berhubungan paling dominan adalah variabel dukungan keluarga dengan nilai Exp (B)= 6.891. Simpulan: Tidak terdapat hubungan antara keterjangkauan geografi dengan kepesertaan JKN. Namun, ada hubungan antara persepsi, dukungan keluarga, pendapatan, dan aksesibilitas informasi serta hubungan paling dominan pada dukungan keluarga dengan kepesertaan JKN. Saran: Masyarakat diharapkan lebih sadar dan berpikir positif terhadap program JKN serta aktif menjadi peserta. BPJS kesehatan perlu memperkuat sosialisasi, khususnya lewat media sosial. Kata Kunci: Aksesibilitas Informasi; Dukungan Keluarga; Jaminan Kesehatan Nasional; Pendapatan; Persepsi.